Site-directed mutagenesis for the production of mutant TP53 Gene and analysis of its tumor suppressor activity - Zafirah Liyana Abdullah (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2011)
As a cellular gatekeeper, p53 plays a major role in maintaining the cellular homeostasis. The existence of mutations may change the gene conformation and may affect its major function as the regulator of the cell proliferation. The p53 therapy based approach is a good candidate for treatment of TP53-defect cancers. However, this treatment is unsuitable for some cancer cases, especially those caused by dominant-negative activity of the mutant p53 protein. Dominant-negative occur in the presence of a mutated allele which results in the formation of heterotetramer of endogenous wild-type/mutant p53 that are unable to transactivate certain p53 downstream target genes, which are important for the cells regulation. Thus, more effective treatment is needed to overcome this problem and DNA vaccination may be the suitable candidate. A recombinant mutant p53 designated as R248Q has been put forward as a potential antigen for the DNA vaccination strategy. Therefore, the current research aims to produce mutant TP53R248Q through PCR site–directed mutagenesis and to confirm the tumor suppression ability of TP53R248Q. The mutation of R248Q was generated via Polymerase Chain Reaction (PCR) site-directed mutagenesis to pCMVp53 plasmid by using a set of specifically constructed primers. Subsequently, these constructed TP53R248Q and TP53 gene was transfected into the TP53-null H1299 cell lines. Following that, phenotype and genotype expression studies on the cell lines were performed by colony formation assay and quantification of a TP53 downstream target gene p21waf1, respectively, in order to investigate the tumor suppression ability of the mutated TP53. In phenotype study, the transfection with exogenous TP53 suppressed the colony growth while the treatment with TP53R248Q confirmed the loss of p53 original function by its inability to restrain cell proliferation. The result of phenotype study was confirmed by the expression analysis of downstream TP53 gene, p21waf1. Based on the analysis, it was found that the expression of p21waf1 was upregulated in TP53 and downregulated in TP53R248Q treatments. These data therefore confirmed that the PCR site-directed mutagenesis technique has been successfully carried out to induce the desired mutation in the TP53 gene. Thus, this technique may become an interesting option to generate novel recombinant proteins, which may be useful for the development of specifically designed DNA vaccine as a gene therapy strategy for cancer prevention in the future.